Comparison of the insulin action parameters from hyperinsulinemic clamps with homeostasis model assessment and QUICKI indexes in subjects with different endocrine disorders - Skrha, Jan; Haas, Tomás; Sindelka, Gustav; Prázný, Martin; Widimský, Jirí; Cibula, David; Svacina, Stepán (The Journal of clinical endocrinology and metabolism, 2004)
The aim of this study was to compare insulin sensitivity expressed by the hyperinsulinemic clamp and by the homeostasis model assessment (HOMA) and QUICKI indexes in subjects with various disorders influencing insulin action. We examined 41 type 2 diabetic patients, 20 insulinoma patients, 32 women with polycystic ovary syndrome, 16 patients with primary hyperaldosteronism, 12 patients with essential high renin hypertension, and 47 healthy subjects. The metabolic clearance rate of glucose and the insulin sensitivity index calculated from the clamps were compared with both the HOMA and QUICKI indexes. The relationship of insulin action to body mass index, serum cholesterol, and triglycerides as well as to systolic and diastolic blood pressures was also evaluated. Body mass index was very strongly associated with the insulin sensitivity index (r = -0.70; P < 0.0001) in the entire cohort of 168 subjects. Cholesterol, triglycerides, and blood pressure influenced insulin action in the healthy subjects and type 2 diabetic patients. A significant relationship was observed between the insulin sensitivity index and the HOMA or QUICKI indexes in healthy subjects (r = -0.66; P < 0.0001), type 2 diabetic patients (r = -0.68; P < 0.0001), and women with polycystic ovary syndrome (r = -0.65; P < 0.0001). We did not find any relationship between the above variables in the patients with insulinoma or primary hyperaldosteronism. The HOMA and QUICKI indexes do not offer the same information as glucose clamps in the rare cases with differently impaired peripheral or hepatic insulin action.
Keywords: hypertenze; Cholesterol; metabolická clearance; nádory slinivky břišní; lidé středního věku; triglyceridy; homeostáza; Polycystic Ovary Syndrome; krevní tlak; nemoci endokrinního systému; inzulinová rezistence; Humans; Pancreatic Neoplasms; Glucose Clamp Technique; Middle Aged; Insulinoma; senioři; Metabolic Clearance Rate; cholesterol; Endocrine System Diseases; Female; mladiství; glykemický clamp; Blood Pressure; index tělesné hmotnosti; inzulin; Aged; Hyperaldosteronism; hyperaldosteronismus; ženské pohlaví; Insulin; inzulinom; Body Mass Index; Diabetes Mellitus, Type 2; Adult; syndrom polycystických ovarií; Insulin Resistance; Homeostasis; Adolescent; Triglycerides; Hypertension; dospělí; lidé; diabetes mellitus 2. typu